Do Interest Groups affect US Immigration Policy? - Giovanni Facchini; Anna Maria Mayda; Prachi Mishra (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2009)
While anecdotal evidence suggests that interest groups play a key role in shaping immigration policy, there is no systematic empirical analysis of this issue. In this paper, we construct an industry-level dataset for the United States, by combining information on the number of temporary work visas with data on lobbying activity associated with immigration. We find robust evidence that both pro- and anti-immigration interest groups play a statistically significant and economically relevant role in shaping migration across sectors. Barriers to migration are lower in sectors in which business interest groups incur larger lobby expenditures and higher in sectors where labor unions are more important.
Keywords: F22; J61; 330; Immigration; Immigration Policy; Interest Groups; Political Economy